Safety and tolerability of intravenous immunoglobulin in patients with active dermatomyositis: results from the randomised, placebo-controlled ProDERM study - Rohit Aggarwal; Joachim Schessl; Christina Charles-Schoeman; Zsuzsanna Bata-Csörgő; Mazen M. Dimachkie; Zoltan Griger; Sergey Moiseev; Chester V. Oddis; Elena Schiopu; Jiri Vencovský; Irene Beckmann; Elisabeth Clodi; et al. (Arthritis Research & Therapy, 2024)
Abstract Background Dermatomyositis is an idiopathic inflammatory myopathy characterised by rashes and progressive muscle weakness. The recent ProDERM (Progress in DERMatomyositis) study is the first large randomised, placebo-controlled trial to establish the efficacy and safety of intravenous immunoglobulin (IVIg) in adult patients with dermatomyositis. Objectives of this analysis were to closely examine the safety and tolerability of IVIg in patients from the ProDERM study. Methods ProDERM was a double-blind, randomised, placebo-controlled, multicentre, phase 3 study. In the first period (weeks 0–16), adults with active dermatomyositis received 2.0 g/kg IVIg (Octagam 10%; Octapharma AG) or placebo every 4 weeks. In the open-label extension period (weeks 16–40), all patients received IVIg for 6 additional cycles; dose reduction (1.0 g/kg) was permitted if patients were stable. Treatment-emergent adverse events (TEAEs) were documented. Results The 95 patients enrolled were randomised to receive IVIg (N = 47) or placebo (N = 48) in the first period, with 5 switching from placebo to IVIg. Overall, 664 IVIg infusion cycles were administered. During the first period, 113 TEAEs were possibly/probably related to treatment in 30/52 patients (57.7%) receiving IVIg and 38 in 11 patients (22.9%) on placebo. Eight patients discontinued therapy due to IVIg-related TEAEs. Eight thromboembolic events (TEEs) occurred in six patients on IVIg; six in five patients were deemed possibly/probably related to IVIg. Patients with TEEs exhibited more baseline TEE risk factors than those without TEEs (2.4–15.2-fold higher). Lowering infusion rate reduced the rate of TEEs, and none occurred at the lower IVIg dose. No haemolytic transfusion reactions or deaths occurred. Conclusions Results from this study demonstrate that IVIg has a favourable safety profile for treatment of adult dermatomyositis patients and provides evidence that will help to inform treatment choice for these patients. Dermatomyositis patients receiving high-dose IVIg should be monitored for TEEs, and a low rate of infusion should be used to minimise TEE risk, particularly in those with pre-existing risk factors. Trial registration ProDERM study (NCT02728752).